Pemanfaatan Limbah Buah Naga Menjadi Sumber Potensi Baru Dalam Pemberdayaan di Desa Trenggulunan Melalui Inovasi Sosial Mbah Ganteng - Jayadi Jayadi; Bambang Apriyanto; Edi Saputra; Vernando Pratama Putra; Dimas Aji Prastyo (CV. Green Publisher Indonesia, 2026)
This study addresses the environmental and economic challenges arising from the accumulation of dragon fruit waste in Trenggulunan Village, Rembang Regency, where up to 40% of total harvest remains unmarketable and contributes to soil degradation. The research aims to analyze the implementation and impact of the social innovation program MBAH GANTENG (Organic Waste and FABA Management for Trenggulunan Environment) as a community empowerment strategy. A qualitative descriptive-exploratory method was employed, utilizing in-depth interviews, observations, and documentation to examine program processes and outcomes. The findings reveal that the innovation successfully transforms agricultural, household, and industrial waste (Fly Ash Bottom Ash/FABA) into valuable organic agricultural products such as Booster FABA fertilizer, silica fertilizer, hydroton, and biowasil. The results demonstrate significant improvements in soil quality, including increased pH from acidic to neutral, enhanced organic carbon, nitrogen, phosphorus, and potassium levels, and improved soil fertility index. Additionally, the program reduced agricultural waste by 80.3%, increased harvest frequency from two to four cycles annually, and generated economic benefits through increased farmer income and cost efficiency. Socially, the initiative fostered behavioral change in waste management and strengthened community participation. In conclusion, MBAH GANTENG represents an effective, sustainable, and replicable model of circular economy-based social innovation that simultaneously addresses environmental, economic, and social issues